TAX BALANCE IN AGRIBUSINESS AS A TYPE OF SPECIAL BALANCE - Milojević, Ivan; Zekić, Milorad; Gobeljić, Zvonko (Economics of Agriculture, 2015)
The tendency of continuous compounding of business processes inevitably leads to application of increasingly complex instruments for the purposes of fnancial reporting in agribusiness. In this system the existential place and role of individual elements that alter the existing and acquire new functions comes into question. Balancing implies a regulated and consistent system in which every change leads to the creation of new relations and changing already established relationships. In this regard, in this paper we will focus on the place and role of tax balance in the group of special balances in agribusiness, as a very signifcant group of accounting instruments. Displaying information for users and situations in which they are used, balances gain their place in this classifcation. For the purposes of applying fnancial instruments, referring primarily to balances in agribusiness, it is necessary to know the way of their classifcation according to their functions. From this aspect, tax balance in agribusiness is a specifc report, both in terms of its formal and material structure, which gives it the basis to belong to ordinary as well as special types of balances in agribusiness.